A History of Pashtun Migration : 1775-2006 - Nichols, Robert (Karachi, Pakistan Oxford University Press, 2008)
"For centuries Pashtuns from the Peshawar Valley and today's Pakistan-Afghan borderlands have circulated throughout the sub-continent and the Indian Ocean region. This interregional history of migration and mobility in the modern period from 1775 to 2006 follows Pashtun individuals and communities as they left homelands and responded to colonial and post-colonial opportunities and challenges in eighteenth century Rohilkhand, nineteenth century northern India and Hyderabad, Pakistan after 1947, and the Gulf region from the nineteenth century to the present. Pashtuns in permanent or temporary diaspora were transformed by the range of possible social consequences as they circulated in South Asia and the greater Indian Ocean region, variously experiencing degrees of assimilation, integration, sustained ethnic self-awareness, and, increasingly, notions of "national" identity. Pashtuns in home villages and in distant locations exhibited personal initiative and agency even as they were affected by wider European imperial policies, national and interregional political competition, and the evolving pressures of an expanding world economy. This work illuminates the history of Pashtuns and Pakistan and offers insight into how Asian regional populations have been integrated into, and often subordinated by, the dynamics of contemporary globalization."--Jacket.
Include Index, Maps and Bibliography
Keywords: Pushtuns -- Pakistan--Peshawar Region